Observations and analysis of the impact of annular eclipse on 10 MHz short-wave signal in Sanya area on June 21, 2020 - Luxi Huang (AIP Publishing LLC, 2021)
This paper takes the annular solar eclipse that occurred in China on June 21, 2020, as the background and conducts tests and analysis of shortwave timing sky wave signals. The test group continuously tested the signal field strength data from June 20, 2020, to June 23, 2020. The results show that the shortwave signal field strength on June 21, the day of the annular eclipse, is significantly weaker than that on two other days—before and during the annular eclipse—and there are three obvious jumps in the field strength value. (1) The first jump occurs more than one hour before the annular eclipse, and then, the field strength has an oscillatory attenuation. Between the first jump and the second jump, the overall change trend of the field strength value is an oscillatory decline one. (2) About 25 min before the beginning of the eclipse, the second jump of the field strength occurs; from the second jump to the third jump, that is, before the occurrence of the beginning of the eclipse and the transition phase from the beginning to the middle of the eclipse, the value of the field strength has an oscillatory increase. (3) During the period of 8:00–8:10, the field strength shows a third jump. Although the field strength oscillates after the third jump, it has no obvious increasing or decreasing trend. Based on the results of previous studies on the annular eclipse on that day and the analysis of the theoretical model of radio wave propagation, this paper preliminarily considers that the change in signal field strength is supposed to be caused by the impact of the outbreak of the annular eclipse on the ionosphere. When the annular eclipse occurred, the sunlight reaching the ground is blocked by the Moon, and the ionization degree of electrons in the ionosphere is reduced, resulting in an increase in the penetration factor, and the overall performance of the shortwave signal reaching the ground is weakened.